2021
DOI: 10.1038/s41467-021-26452-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying previous SARS-CoV-2 infection through mixture modelling of antibody levels

Abstract: As countries decide on vaccination strategies and how to ease movement restrictions, estimating the proportion of the population previously infected with SARS-CoV-2 is important for predicting the future burden of COVID-19. This proportion is usually estimated from serosurvey data in two steps: first the proportion above a threshold antibody level is calculated, then the crude estimate is adjusted using external estimates of sensitivity and specificity. A drawback of this approach is that the PCR-confirmed cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…22,23 A key limitation of the study is that we were unable to fully account for waning of antibodies, which could have led to an underestimation of seroprevalence. In a previous study, we undertook mixture modelling, 24 which does not rely on thresholds, but instead assumes that the population sampled consists of two groups with different distributions of antibody levels; this suggested that the threshold-based method was significantly underestimating the true seroprevalence. We were however unable to conduct similar analysis for this dataset, as the mixture modelling requires control data from the respective sites which we did not have.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A key limitation of the study is that we were unable to fully account for waning of antibodies, which could have led to an underestimation of seroprevalence. In a previous study, we undertook mixture modelling, 24 which does not rely on thresholds, but instead assumes that the population sampled consists of two groups with different distributions of antibody levels; this suggested that the threshold-based method was significantly underestimating the true seroprevalence. We were however unable to conduct similar analysis for this dataset, as the mixture modelling requires control data from the respective sites which we did not have.…”
Section: Discussionmentioning
confidence: 99%
“…Given these limitations, mixture models have been proposed 19 and used previously to perform inference on serological data [20][21][22] . A major strength of these approaches is that they infer seropositivity using the distribution of raw antibody values in the population, obviating the need for a strict, binary cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence is currently highest in Nairobi, then Busia, then Kilifi, correlating with the counties' population densities. In Nairobi, in August 2020, just after the peak of the first wave of SARS-CoV-2 infections, mixture modelling, which attempts to account for the wide range of OD ratios among those exposed to the virus better than the simple threshold analysis (20), indicates a cumulative incidence of 75%, just 4 months after the start of the pandemic. At the same timepoint, 6,727 PCR-confirmed infections had been registered across the city (<1% of the County's population; Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%